Pengaruh Pemotongan Bagian Tubuh Terhadap Respon Fisiologi Dan Perilaku Ikan Nila (Oreochromis niloticus) Dan Ikan Lele (Clarias gariepinus) - Halawa, Alfriend John Saotama; Zai, Desniwati (CV. SINAR HOWUHOWU, 2024)
This study examines the effect of cutting body parts, such as dorsal, pectoral, ventral, anal, caudal and lateral fins, on the physiological and behavioral responses of tilapia (Oreochromis niloticus) and catfish (Clarias gariepinus). The study was conducted through an experimental approach by cutting fish body parts, then observing changes in physiology (such as stress hormone release) and behavior (swimming activity, social interaction). Results showed that injury significantly affected swimming efficiency, body balance, sensory responses, as well as increased stress characterized by cortisol release. Injury also altered fish behavior, including reduced activity and a tendency to hide. Morphometric and meristic analyses revealed that body damage impacted the body size and adaptability of the fish. This study emphasizes the importance of good aquaculture management, including water quality and nutrition, to support tissue regeneration, fish welfare and farm productivity. The findings provide important insights for sustainable aquaculture practices.